Novel Cyano‐Artemisinin Dimer ZQJ29 Targets PARP1 to Induce Ferroptosis in Pancreatic Cancer Treatment - Jianping Chen; Lingyun Yue; Yanna Pan; Bingying Jiang; Junfeng Wan; Haixia Lin; Fujiang Guo; Huiyu Li; Yajuan Li; Qingjie Zhao (Advanced Science)
Abstract Pancreatic cancer remains one of the most lethal malignancies in the digestive system, with limited available drugs and a need for improved efficacy. This unmet clinical need highlights the urgency to discover novel, highly efficient small‐molecule compounds. Herein, a novel cyano‐containing artemisinin dimer derivative, ZQJ29, is synthesized through structural modifications of artemisinin. Biological evaluation demonstrated that ZQJ29 effectively inhibits the proliferation of pancreatic cancer cells both in vitro and in vivo. ZQJ29 selectively targets PARP1 and has distinct structural features comparable to established PARP1 inhibitors such as Olaparib. Notably, ZQJ29 is the first reported artemisinin derivative to inhibit PARP1. Furthermore, the inhibition of PARP1 by ZQJ29 enhances the expression of TP53 and inhibits the SLC7A11/GPX4 pathway. The work first demonstrates that targeting PARP1 can induce ferroptosis in pancreatic cancer. These findings not only identify promising artemisinin derivatives for the development of therapies targeting pancreatic cancer but also provide scientific evidence supporting therapeutic strategies aimed at inducing ferroptosis in pancreatic cancer. This research lays a robust foundation for subsequent preclinical studies.